Determination of Total Phenolic Levels of Ethyl Acetate Fraction of Clove Leaves (Syzygium aromaticum (L) Merr) - Arniati, Arniati; Pratama, Mamat; Baits, Muzakkir; Tahir, Masdiana (Pharmaceutical Reports, 2022)
Clove is a spice plant used in the kretek cigarette industry, food, beverage, and medicine. Clove leaves contain chemical compounds, namely saponins, flavonoids, tannins, and essential oils. The exploration of clove leaves has not been maximally carried out. Therefore, this study aims to determine the total phenolic content in the ethyl acetate fraction of clove leaves by using gallic acid as a comparison. Clove leaves were powdered and then macerated by ethanol. The ethanol extract was dissolved in distilled water and it was fractionated with ethyl acetate on a separating funnel. The method used in this assay is the UV-Vis spectrophotometry technique. The qualitative analysis was performed by adding the FeCl3 reagent. The results showed that the ethyl acetate fraction of clove leaves contained a total phenolic compound of 65.52 mg gallic acid equivalent per gram of extract (GAE/g). Thus, the ethyl acetate fraction of clove leaves is feasible to be developed as a source of phenolic compound.